PURIFICATION OF ETHANOL BY CONTINUOUS ADSORPTION METHOD USING ZEOLITE 3A AND CALCIUM OXIDE - Mukhtar Anas Ibrahim; Muhammad Hafizh Musyaffa; Heriyanto; Haryadi (Jurnal Kimia Riset, 2022)
The depletion of oil reserves and the increasing need for fuel have become a problem in the supply of energy sources. One of the efforts to maintain the availability of fuel is to use ethanol fuel grade as an alternative fuel. Continuous adsorption is one method that can purify ethanol up to a concentration of 99.5% (v/v). This study aims to increase the purity of ethanol using adsorbent zeolite 3A and calcium oxide (CaO) with a continuous adsorption method. The feed used is technical ethanol with a concentration of 96% (v/v). The equipment used is a continuous adsorption apparatus with a fixed bed column. Parameters measured during the process were ethanol concentration, feed flow rate, temperature, and pressure. Variations carried out were variations in feed flow rate (5 mL/min, 12 mL/min, and 18 mL/min) and the type of adsorbent (zeolite 3A and CaO). The best continuous adsorption process at 5 mL/min flow rate using zeolite 3A adsorbent with the ethanol product concentration rated up to 99.54% on pycnometer analysis and 99.33% on GC-MS analysis. While using CaO adsorbent, the best results were obtained at 5 ml/min rate, with the highest ethanol product concentration of 99.54% in the pycnometer and 99.33% on GC-MS.